Matching in thin labour markets: panel data evidence from Finland, 1991-2002 - Aki Kangasharju; Jaakko Pehkonen; Sari Pekkala (European Regional Science Association (ERSA), 2003)
The matching function that postulates a relationship between the flow of new matches and stock of job seekers and vacancies has attracted considerable attention, both theoretical and empirical during the last decade. In this paper the properties of a matching function are examined by using a large panel data set from Finland. The data has a high frequency and it is highly disaggregated, comprising monthly data on 174 work-to-travel areas from a 12-year period between January 1991 and August 2002. We test for density effects, i.e. the importance of the size of markets on matching efficiency. The robustness and importance of our empirical findings are guaranteed by the quality of data. First the data allows us to model matching functions for two different measures of endogenous variables, namely total matches and total outflow from unemployment. Second, we can measure job seekers by their origin, i.e. whether they are unemployed, employed or outside of the labour force. We can thus construct matching models where the measure of job matches and the pool of job searchers are consistent with each other. Third, the data includes information on the composition of the registered job seekers, including age, sex and the share of short- and long-term unemployment. These controls provide interesting information on possible differences in matching rates by these groups.
Keywords: 330